(untitled) (Docentes 2.0 Journal, 2025)
Conflicts in the classroom are inevitable events that reflect students’ social and emotional dynamics. The research aimed to analyze the role of the teacher as a mediator in resolving conflicts within the classroom, promoting a culture of peace, and strengthening school coexistence. It was based on a systematic method, an interpretive paradigm, a qualitative approach with a descriptive narrative design, a bibliographic documentary type, and a cross-sectional nature. It included reviewing previous studies by selecting a sample of 8 studies from books and articles consulted in Google Scholar, Scopus, and JSTOR between 2004 and 2024. The results showed that teacher mediation effectively transforms conflicts into learning opportunities, promoting assertive communication, empathy, and collaborative decision-making. Likewise, challenges were identified, such as the lack of teacher training in mediation and the need to establish clear protocols for its implementation in the school environment. It is concluded that the teacher, in his role as mediator, plays a key role in conflict management, promoting an environment of trust and respect that favors learning. It is recommended that research be expanded in different educational contexts and training programs be developed to strengthen teachers’ mediation skills, thus contributing to peaceful and democratic coexistence in educational institutions.